2008
DOI: 10.1515/bc.2009.021
|View full text |Cite
|
Sign up to set email alerts
|

Murine and human cathepsin B exhibit similar properties: possible implications for drug discovery

Abstract: Validation of drug targets and subsequent preclinical studies are usually carried out on animal disease models, with mouse being the most commonly used. However, results from mouse models cannot always be directly related to human disease. Major discrepancies between the properties of murine and human variants were observed during the evaluation of compounds targeting cathepsins S and K. It is important, therefore, to know whether similar differences exist between murine and human cathepsin B. Thus, both enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
4
4
0
Order By: Relevance
“…Human and mouse cathepsin B display similar biochemical properties, and the two enzymes share 83% sequence identity at the amino acid level. 20,21 Mouse cathepsin B effectively hydrolyzed the EVCit linker in EVCit-TFM and displayed similar data to what we observed with human cathepsin B (Supporting Information Figure S7). Evaluation of the Cytotoxicity of EVCit-TFM, EVCit-BFM, and VCit-TFM against Prostate Cancer Cells in the Presence and Absence of TTR.…”
Section: ■ Results and Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Human and mouse cathepsin B display similar biochemical properties, and the two enzymes share 83% sequence identity at the amino acid level. 20,21 Mouse cathepsin B effectively hydrolyzed the EVCit linker in EVCit-TFM and displayed similar data to what we observed with human cathepsin B (Supporting Information Figure S7). Evaluation of the Cytotoxicity of EVCit-TFM, EVCit-BFM, and VCit-TFM against Prostate Cancer Cells in the Presence and Absence of TTR.…”
Section: ■ Results and Discussionsupporting
confidence: 77%
“…We also evaluated the activity of mouse cathepsin B on the hydrolysis of EVCit-TFM. Human and mouse cathepsin B display similar biochemical properties, and the two enzymes share 83% sequence identity at the amino acid level. , Mouse cathepsin B effectively hydrolyzed the EVCit linker in EVCit-TFM and displayed similar data to what we observed with human cathepsin B (Supporting Information Figure S7).…”
Section: Resultssupporting
confidence: 66%
“…Another hint for the possible brain function of Ctsb is that its murine and human variants have similar biochemical properties, and participate in the production of β-amyloid peptides. Thus, lower levels of Ctsb could have both neurotoxic and, under certain conditions, neuroprotective effects by causing a decrease in the amounts of β-amyloid peptides [56], [57], [58].…”
Section: Discussionmentioning
confidence: 99%
“…The prominent functions of cathepsin B in health and disease occur in acidic lysosomes and at the neutral pH of cytosol, nuclei, and extracellular locations. Notably, cathepsin B displays different substrate cleavage properties at the acidic pH compared to neutral pH conditions. It is, therefore, necessary to develop specific substrates for cathepsin B that specifically measure its proteolytic activity over broad pH ranges. Evaluation by this study of current substrates used to monitor cathepsin B activity, consisting of Z-Phe-Arg-AMC and Z-Arg-Arg-AMC, found that they lack specificity since they are cleaved by other cysteine cathepsins; furthermore, Z-Arg-Arg-AMC does not optimally assess cathepsin B activity at acidic pH.…”
Section: Discussionmentioning
confidence: 99%